Exploring the Sub-pillars of Life: Trayopastambha with Special Reference To Nidra - Singh, Priya; S Yadav, S (International Research Journal of Ayurveda & Yoga, 2025)
There has been an unpredictable variation in Trayopstambha: Ahara, Nidra, and Brahmacharya/Abrahmacharya in the modern world as a result of increased urbanization and civilizational advancement, leading to many ailments. Understanding this altered style of life requires an understanding of the Trayopsatambha concept, which aids in leading a healthy existence. The fundamental tool that all people possess to safeguard their destined lives is the Trayopsatambha. Through its close relationship with the three Stambhas of life, it preserves the Swasthya and protects the Ayu. Among all the Upastambhas, Nidra holds a particularly significant role, as it not only supports overall health but also influences the other two – Ahara and Brahmacharya. Therefore, a comprehensive understanding of Nidra, including its definition, physiology, classification, and significance, is essential. Such insight can greatly enhance our appreciation of its vital role in maintaining balance and well-being in daily life.